Small fish consumption in rural Myanmar - Rizaldo, Quennie Vi; Khaing, Wae Win; Belton, Ben (Springer, 2023)
Assessments of fish consumption are based primarily on data from household surveys that do not capture information on the intra-household distribution of the size or species of fish consumed. Such studies can yield partial or misleading information about the adequacy of aquatic food consumption. We address this gap by focusing on individual-level fish consumption within the household, using data from a survey conducted in a rural part of the Ayeyarwady Region in Myanmar—an area with high levels of fish consumption. We disaggregate fish consumption by the gender of household members and by the quantity, species, and size of fish eaten, estimating quantities of fish consumed using models for reference, to identify gendered patterns of fish consumption at the intrahousehold level. We find higher average levels of fish consumption than reported in previous consumption surveys in Myanmar. Moreover, small fish are consumed more frequently than larger-sized fish. The popularity of small fish species highlights the continued reliance of survey respondents on wild fish stocks, despite all surveyed households also practicing small-scale aquaculture. The average consumption of fresh fish reported by women was 36% lower than that reported by men. Men were more likely to eat large fish species, but women ate more small fish, which may contain higher levels of micronutrients vital for addressing nutrient deficiencies.